Analisis Permasalahan Anak Berkebutuhan Khusus (Autis) Dalam Belajar Di Slb Negeri Keleyan Bangkalan - Sri Wahyuning Tiyas; Nova Estu Harsiwi (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research aims to describe the problems of children with special needs (autism) studying at the Keleyan Bangkalan State Special School. Autism is a type of child with special needs (ABK). The type of research used in this study is qualitative research with a descriptive approach. In this research, data was obtained by researchers by conducting interviews, observation, and documentation. The research subjects were children with special needs (autism) at the Keleyan Bangkalan State Special School. The results of the research show that the problems of children with special needs (autism) in studying at the Keleyan Bangkalan State Special School include difficulties in communicating, limited social interaction, behavioral problems, and difficulty concentrating and paying attention. The solution provided to overcome this problem is that the teacher takes an in-depth and structured approach. The teacher creates a friendly learning environment, minimizes environmental stimuli that disturb students, and uses teaching techniques that are adapted to the needs of autistic children.